Brazilian Utilities’ Invoice Data Understanding: Extraction, Data Standardization and Consumption Overview from Partner Universities - Guillardi Júnior, Hildo [UNESP]; de Castro, Marcelo Stehling (Springer Nature, 2023)
Data plays a crucial role in understanding a scientific problem which includes those related to electrical micro, smart grids, and power consumption. In this scenario, one aspect that requires analysis is the consumption data that can be retrieve into the monthly utility invoices. However, the analysis of utility invoices in Brazil poses an unique challenge due to variations in invoice document formats across different services, utilities and contract types. This article addresses this challenge by developing a software based in Regular Expression to extract and standardized data from diverse invoice models. Through the establishment of a database and the use of a Business Intelligence platform, the retrieval and analysis of pertinent information have been significantly improved. The focus of this article is on understanding and extracting utility invoice data, including electricity, water, piped gas, and telephony services, which have direct or indirect impacts on natural resources and human well-being. The analysis is carried out on public buildings in Brazil, specifically those associated with the São Paulo Center for Energy Transition Studies (CPTEn). The data presented in this paper encompasses consumption invoices from three universities: the State University of Campinas (Unicamp), São Paulo State University campus of São João da Boa Vista (Unesp-SJBV), and the Federal University of Goiás (UFG). It is important to note that all the analyzed information is publicly available under Brazilian law number 12 527 from November 18, 2011.